Sponsorship effectiveness: consumer recall, recognition and perceptions of official sponsorship and ambush marketing in the 2010 FIFA World Cup™ - Rabale, Emmanuel (Vaal University of Technology, 2012)
The phenomenal growth of special events sponsorship as a promotional tool is evident in the increase in the number of companies and their expenditure on sponsoring events. Currently, football (for the purpose of this study, the term football and soccer are used interchangeably) has become the most heavily sponsored sport in terms of value and number of sponsorship deals. International events such as the Federation of International Football Association (FIFA) World Cup™ and the Olympic Games are the biggest sporting events staged globally which makes them particularly lucrative for sponsor investment. The high media coverage and duration offers an ideal platform to create high brand awareness, consumer’s recall and recognition for the participating sponsors. The FIFA Soccer World Cup™ tournament with its huge audience is perhaps the premier place for companies to display their brands on an international stage. Millions of rands are spent on sponsorship in general every year and on sports sponsorship in particular. Yet little is known about the effectiveness of this expenditure. Sponsors are often unsure whether only their brands benefit from a sponsorship or whether competing brands in the same product category also benefit from their efforts. The primary objective of this study was to determine sponsorship effectiveness through consumers recall and recognition. In addition, the study sought to determine the perception of official sponsorship and ambush marketing during the 2010 FIFA World Cup™. The event attracts billions of viewers and a huge number of companies associate their products with this event. A quantitative approach was adopted for the study. The data was collected using a convenience sample of 462 fans, supporters and followers of the 2010 FIFA Soccer World Cup™ in Gauteng, South Africa. To determine sponsorship effectiveness, consumer-aided and unaided recall tests were conducted after the 2010 FIFA World Cup™ in an attempt to quantify sponsorship recall of official and non-official responses In addition, the study sought to establish consumers’ perceptions of official sponsors and the purchase intentions of their products and brands. Finally, consumers perceptions towards unofficial (ambush marketers) sponsors were ascertained. The high frequency of inaccurate responses through unaided recall suggests that there was confusion in the minds of respondents regarding those who were official sponsors of the 2010 FIFA World Cup™. This has serious implications for both marketers and sponsors as the effectiveness of sponsorship as a marketing communication tool comes into question. This may work to the advantage of ambush marketers who could effectively use the confusion in consumers’ minds to market their products and brands. Possible reasons for the inaccurate responses could be attributed to the fact that the World Cup™ is a once-off event that attracts individuals because of the novelty of the event and the multiple distractions that are associated with the event. The inaccurate responses may also have implications for future purchase intentions of the product since a recall level of awareness could be a determining factor in the purchase decision. This study revealed that sponsorship recall is enhanced by aided recall and prior knowledge of the sponsor. The responses with regard to aided recall suggest that consumers were able to recognise brands that were housed and marketed in South Africa. Brands such as Seara, Yingu Solar, Satyam, NeoAfrica, Aggreko and Prasa are relatively unknown brands in South Africa – therefore they were not easily recognised by the respondents. From a marketing perspective, the question arises whether it is feasible for foreign-based companies such as Emirates and Mahindra Satyam to invest in sponsorship ventures that are unlikely to achieve the desired results. These companies did not widely advertise in the local South African market. However, because the 2010 FIFA World Cup™ had a worldwide impact, this does not mean that global brands failed to achieve their objectives elsewhere in the world. In other words, they could have been playing to a much wider audience, in much stronger markets than that of the host country. An interesting revelation was that most consumers were able to recall brands that were global, mass-marketed and consumer-oriented such as Coca-Cola and McDonalds. This may partially be because during the event they were intensively engaged in advertising their sponsorship in the 2010 FIFA World Cup™.
M. Tech. (Department of Marketing, Faculty of Management Sciences), Vaal University of Technology.
Keywords: Sponsorship -- Special events; Companies -- Sponsorhip; Companies -- Promotion; FIFA World Cup; Federation of International Football Association World Cup; Sponsorship effectiveness; 658.82; Sports sponsorship.; Corporate sponsorship.; Sports -- Econonomic aspects.; Sports -- Public relations.; Dissertations, Academic -- South Africa.